Business Development Strategy Songket Nagari Pandai Sikek X Koto Sub-District (Sumatra Journal of Disaster, Geography and Geography Education, 2023)
This study seeks to examine the strategy of developing songket craft business in increasing income in Nagari Pandai Sisek, X Koto District. This type of research is descriptive, which aims to find out the value of the independent variable without connecting or making comparisons with other variables. The data used in this study is qualitative data in the form of answers through interviews and literature studies. In analyzing data using SWOT analysis techniques. The results of this study show that there is still a need for a market development strategy by expanding cooperation with travel and tourism buses that will take visitors to the songket crafts center. Including improving access and widening roads to facilitate vehicles coming both at home and abroad. In addition, it also needs to expand marketing through social media.